GIS-based Bivariate Analysis of the Impact of Climate on the Abu Dhabi (UAE) Mangrove National Park - A. Raihan; T. Ali; Md. M. Mortula (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
Mangrove is a vital natural resource, satisfying the various demands of both humans and other aquatic habitats. Also, it shields against natural disasters. Extensive researches were conducted on the benefits of mangrove to combat climate change. But limited works were done to assess the impact of microclimate factors on mangrove. This study examined the impact of climate represented by Land Surface Temperature on mangrove forest health (i.e., Normalized Difference Vegetation Index) for Abu Dhabi Mangrove National Park, covering the period: 2015–2020. To accomplish this, Local Bivariate Analysis was performed. Firstly, satellite images from Landsat 8 covering the study area were downloaded and pre-processed. Then, values of the variables were computed, extracted as points and then analysed. Results showed that the mangrove exhibited different temperature and vegetation health relationships (i.e., Positive Linear, Negative Linear, Concave, Convex, Not Significant, etc.). Also, results showed that mangrove health has degraded due to surface temperature increase. Furthermore, the coefficient of determinations of the bivariate analysis of the mangrove and the land surface temperature in 2020 is higher compared to that of 2015 with the highest R2 = 0.8512 (Convex) followed by R2 = 0.8192 (Concave) and R2 = 0.7281 (Negative Linear).